Disclosure of a Promising Lead to Tackle Complicated Skin and Skin Structure Infections: Antimicrobial and Antibiofilm Actions of Peptide PP4-3.1 - Ana Gomes; Lucinda J. Bessa; Iva Fernandes; Ricardo Ferraz; Cláudia Monteiro; M. Cristina L. Martins; Nuno Mateus; Paula Gameiro; Cátia Teixeira; Paula Gomes (Pharmaceutics, 2021)
Efficient antibiotics are being exhausted, which compromises the treatment of infections, including complicated skin and skin structure infections (cSSTI) often associated with multidrug resistant (MDR) bacteria, methicillin-resistant S. aureus (MRSA) being the most prevalent. Antimicrobial peptides (AMP) are being increasingly regarded as the new hope for the post-antibiotic era. Thus, future management of cSSTI may include use of peptides that, on the one hand, behave as AMP and, on the other, are able to promote fast and correct skin rebuilding. As such, we combined the well-known cosmeceutical pentapeptide-4 (PP4), devoid of antimicrobial action but possessing collagenesis-boosting properties, with the AMP 3.1, to afford the chimeric peptide PP4-3.1. We further produced its N-methyl imidazole derivative, MeIm-PP4-3.1. Both peptide-based constructs were evaluated in vitro against Gram-negative bacteria, Gram-positive bacteria, and Candida spp. fungi. Additionally, the antibiofilm activity, the toxicity to human keratinocytes, and the activity against S. aureus in simulated wound fluid (SWF) were assessed. The chimeric peptide PP4-3.1 stood out for its potent activity against Gram-positive and Gram-negative bacteria, including against MDR clinical isolates (0.8 ≤ MIC ≤ 5.7 µM), both in planktonic form and in biofilm matrix. The peptide was also active against three clinically relevant species of Candida fungi, with an overall performance superior to that of fluconazole. Altogether, data reveal that PP4-3.1 is as a promising lead for the future development of new topical treatments for severe skin infections.